β-Glucosidase VmGlu2 Contributes to the Virulence of Valsa mali in Apple Tree - Huang, Yan; Yu, Chunlei; Sun, Cuicui; Saleem, Muhammad; Li, Pingliang; Li, Baohua; Wang, Caixia (Frontiers in Microbiology, 2021)
The apple tree canker is caused by Valsa mali, which produces major pathogenic factors involving multiple cell wall-degrading enzymes (CWDEs) and toxins. The β-glucosidases are among the main CWDEs, and thus, they play important roles in the virulence of necrotrophic pathogens. However, the specific roles of β-glucosidases in the virulence of V. mlai remain largely unknown. In this study, we identified a β-glucosidase gene, VmGlu2, which was upregulated during the V. mali infection. We found that VmGlu2 protein had high enzyme activity of β-glucosidase using pNPG as a substrate, while the VmGlu2 could convert phloridzin to phloretin with the release of glucose. The deletion and overexpression of VmGlu2 showed no effect on vegetative growth, but gene deletion mutants of V. mlai showed significantly reduced pycnidia formation. The gene deletion mutants had lower β-glucosidase activities and toxin levels as compared to the wild-type strain. Therefore, these mutants showed a reduced virulence. Moreover, the overexpression of VmGlu2 did not affect toxin levels, but it significantly enhanced β-glucosidase activities, which resulted in an increased pathogenicity. Thus, we conclude that VmGlu2 is required for the full virulence of V. mali. These results provide valuable evidence to the complex role of CWDEs in the fungal pathogenicity.